2005
DOI: 10.1682/jrrd.2005.03.0061
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive enhancement therapy with work therapy: Productivity outcomes at 6- and 12-month follow-ups

Abstract: Abstract-Neurocognitive enhancement therapy (NET), which involves computerized cognitive training and other methods, has been shown to improve working memory and executive function in schizophrenia. In the present study, 145 outpatients with diagnoses of schizophrenia or schizoaffective disorder recruited from a Department of Veterans Affairs mental hygiene clinic and from a community mental health center were randomized to 6 months of paid work therapy (WT) or to NET+WT. Mixed random effects analyses revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 37 publications
1
97
0
4
Order By: Relevance
“…As with other cognitive rehabilitation programs, these results were based on assessments made at the end of the active phase of the intervention. Subsequently, we reported that participants in NET + WT worked more hours than those in WT, with differences emerging during the 6 months following the active intervention [23]. We also found that improvements in work functioning were greatest for those who responded to the NET training by reaching normal levels of performance on a trained working memory task.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…As with other cognitive rehabilitation programs, these results were based on assessments made at the end of the active phase of the intervention. Subsequently, we reported that participants in NET + WT worked more hours than those in WT, with differences emerging during the 6 months following the active intervention [23]. We also found that improvements in work functioning were greatest for those who responded to the NET training by reaching normal levels of performance on a trained working memory task.…”
Section: Introductionmentioning
confidence: 68%
“…Based on our previous findings that improvement in cognitive performance on NET-trained tasks endured to follow-up [16] and that work outcomes differentially improved for NET + WT during follow-up [23], we expected this would be the case for NET + WT effects on neuropsychological performance. Specifically, we hypothesized that executive function and working memory gains observed at the end of treatment would still be detectable 6 months later.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the relationship of cognitive-remediation-linked improvements in working memory, or non-specific improvements in working memory, reasoning/problem-solving, verbal and non-verbal episodic memory, and processing speed observed in this study, to performance-based, proxy measures of daily-life functioning and actual measures of community-function, remains unclear. We note that integration of cognitive remediation interventions similar to the type employed in the current study with work therapy or supported employment programs have produced improvements in measured work function (Bell et al, 2005;McGurk et al, 2005). We are currently conducting studies to investigate the relationship of the improved cognitive skills evident in the current study to proxy and actual measures of community function.…”
Section: Discussionmentioning
confidence: 86%
“…Data from intervention studies (as well as studies described above) have not been universally supportive of a direct link between cognition and action. Substantial evidence from a number of studies [90][91][92][93] suggests that cognitive remediation acts as a mediator of the effects of cognitive change on outcome. The key components of this model include processes involved with the transfer to community functioning (including metacognition) and cognitive schema.…”
Section: Statistical Issuesmentioning
confidence: 99%